Occurrence of Chronic Pulmonary Aspergillosis in Pulmonary Tuberculosis: A Hospital-Based Cross-Sectional Study - Priyadarshani, Shivangi; Choubey, Satyadeo; Ejazi, Arshad; Shankar, Manish; Kumar, Shailesh; Kumari, Rekha (Nigerian Medical Journal, 2026)
Background: Chronic pulmonary aspergillosis (CPA) is a recognized complication in patients with pulmonary tuberculosis, particularly in high TB burden regions. Misdiagnosis and inappropriate treatment occur due to overlapping clinicoradiological features, leading to increased morbidity and mortality. Data on CPA occurrence and its association with PTB in tertiary care settings remain limited in resource-constrained countries. Methods: This study enrolled 143 adults from outpatient and inpatient departments. Newly and previously diagnosed PTB patients were included. The CPA diagnosis was based on symptoms lasting over three months, radiological findings, and microbiological/immunological evidence using Aspergillus IgG and BAL galactomannan testing. Data were analyzed using STATA 14.0. Descriptive statistics summarized demographic and clinical data, and comparative analyses between CPA and non-CPA groups used chi-square or Fisher's exact tests for categorical variables and Student's t-test for continuous variables. Results: CPA was diagnosed in 34.3% (49/143) of PTB patients. The CPA cohort showed male predominance (male-to-female ratio, 4:1), with associations with diabetes mellitus (70.8%, p=0.038) and post-tuberculosis lung disease (61.4%, p=0.040). Radiological features, including cavitation (47.4%, p=0.009), aspergilloma (55.9%, p=0.009), and infiltrates (72.3%, p=0.10) were more frequent in CPA patients. Aspergillus-specific IgG was positive in 69.4% (p<0.001) and BAL galactomannan in 43.9% (p<0.001) of CPA patients. Conclusion: CPA is prevalent among PTB patients, especially those with TB history and comorbidities like diabetes. Integrated diagnostic approaches, including immunological and antigen testing, are recommended to improve differentiation and management in resource-limited settings.